Kesan penghargaan kendiri sebagai moderator ke atas hubungan antara kesedaran keselamatan dan iklim keselamatan - Md. Baharudin, Mohd. Hakimi (2014)
Safety problem needs to be highlighted as the accident rate among employees is increasing. Thus, there is a need to focus on safety problem among the employees themselves in terms of self-esteem, safety awareness and safety climate. These factors are important as they are directly to the employees. However, previous research has addressed the issues of safety without considering self-esteem as a psychological aspect. The main purpose of research is to identify the effect of self-esteem in moderating the relationship between safety awareness and safety climate. In this quantitative study, a set of questionnaire focusing on safety awareness, safety climate, and self-esteem was used to collect data. 256 employees among the operators at the body assembly section of PERODUA, Rawang Manufacturing Plant were selected to participate in the study. Descriptive statistics (frequency, percentage, mean and standard deviation) and inferential statistics (simple linear regression and multiple regressions) were used to analyse the data. The findings showed that safety awareness among the employees was at a high level while the safety climate was at moderate level. Besides that, the research findings proved that there was a significant effect of safety awareness on safety climate. The findings also showed that the effect of self-esteem moderated the relationship between safety awareness and safety climate. Based on the results, it is recommended that the safety department include the staff from the psychology department to address safety issues. Besides that, safety training has always been given as a generalised practice and this study proposes that safety training should be geared towards job specifications.